Genomics of Plasmodium vivax in Colombia reveals evidence of local bottle-necking and inter-country connectivity in the Americas - Sutanto, E; Pava, Z; Echeverry, DF; Lopera-Mesa, TM; Montenegro, LM; Yasnot-Acosta, MF; Benavente, ED; Pearson, RD; Herrera, S; Arévalo-Herrera, M; Trimarsanto, H; Rumaseb, A; et al. (Springer Nature, 2023)
Colombia aims to eliminate malaria by 2030 but remains one of the highest burden countries in the Americas. Plasmodium vivax contributes half of all malaria cases, with its control challenged by relapsing parasitaemia, drug resistance and cross-border spread. Using 64 Colombian P. vivax genomes collected between 2013 and 2017, we explored diversity and selection in two major foci of transmission: Chocó and Córdoba. Open-access data from other countries were used for comparative assessment of drug resistance candidates and to assess cross-border spread. Across Colombia, polyclonal infections were infrequent (12%), and infection connectivity was relatively high (median IBD = 5%), consistent with low endemicity. Chocó exhibited a higher frequency of polyclonal infections (23%) than Córdoba (7%), although the difference was not significant (P = 0.300). Most Colombian infections carried double pvdhfr (95%) and single pvdhps (71%) mutants, but other drug resistance mutations were less prevalent (< 10%). There was no evidence of selection at the pvaat1 gene, whose P. falciparum orthologue has recently been implicated in chloroquine resistance. Global population comparisons identified other putative adaptations. Within the Americas, low-level connectivity was observed between Colombia and Peru, highlighting potential for cross-border spread. Our findings demonstrate the potential of molecular data to inform on infection spread and adaptation.